Physical fitness tests and training interventions for Japanese elite Para badminton players - Kameda, M.; Oishi, M.; Ando, R.; Hakamada, N. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Paralympic badminton has been adopted at the 2020 summer Paralympics in Tokyo. Paralympic badminton can be categorized into wheelchair athletes and standing athletes. So far there has never been researched on physical fitness tests and training interventions for Paralympic badminton athletes. The purpose of this study was to examine the effects of physical fitness tests and training interventions conducted on Paralympic badminton players.